Muckraking : (Bedford Books of St. Martin’s Press, 1994)
Printed together for the first time since their original publication in 1903, Ray Stannard Baker’s piece on the coal strike, "The Right to Work"; Lincoln Steffens’ exposé of political corruption, "The Shame of Minneapolis"; and Ida Tarbell’s story of corporate villainy, "The Oil War of 1872"; along with an editorial from S. S. McClure and the narrative of Ellen Fitzpatrick, invite students to explore and understand "muckraking."